Kinerja Usaha Kecil Berbasis Strategi Bisnis, Budaya Organisasi, dan Kepribadian Pemilik (Studi pada Usaha Kecil di Kabupaten Magetan, Pacitan, dan Ponorogo) - Rohmat Dwi Jatmiko; Eka Afnan Troena; Armanu Thoyib; Ubud Salim (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The aims of this study were to test and analyze empirically the influence of owners’ personality on the small firm organizational culture, on their business strategy orientation, and on the enterprises performance either directly or indirectly. Hypothesis testing was done using empirical data obtained from the questionnaires collected from 365 owners’ of small firms. The testing of hypothesis model used SEM (Structural Equation Modeling) found that the owners’ personalities significantly influenced the organizational culture, and significantly influence the small firm strategy orientation, organizational culture influenced the business strategy orientation, and the owners’ personalities both through organizational culture and business strategy have dominant impact to the performance of their small sized enterprises. The theoretical implication gained in this study was the finding of a theoretical model showing correlation among owner’s personality, organizational culture, business strategy orientation, and their impact to small sized enterprise’s performance. The practical implication of this research suggests that in order to improve small sized enterprises performance, some trainings that meet the personality trait of small sized enterprises owners need to be conducted in order to develop organizational culture and business strategy.Keywords: Personality, Organizational Culture, Business Strategy, Small Sized Enterprise Performance